2020
DOI: 10.1038/s41419-020-03119-z
|View full text |Cite
|
Sign up to set email alerts
|

Mutant CFTR Drives TWIST1 mediated epithelial–mesenchymal transition

Abstract: Cystic fibrosis (CF) is a monogenetic disease resulting from mutations in the Cystic Fibrosis Transmembrane conductance Regulator (CFTR) gene encoding an anion channel. Recent evidence indicates that CFTR plays a role in other cellular processes, namely in development, cellular differentiation and wound healing. Accordingly, CFTR has been proposed to function as a tumour suppressor in a wide range of cancers. Along these lines, CF was recently suggested to be associated with epithelial–mesenchymal transition (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 68 publications
(87 reference statements)
7
36
0
Order By: Relevance
“…However, we also show that in CF epithelia, the TJ protein ZO-1 shows intracellular and diffuse staining and, although SLC26A9 and ZO-1 still appear to co-localize, the integrity of TJ structures is compromised. This is in line with our previous findings (both in lung tissue and immortalized CFBE cells) demonstrating that the presence of mutant CFTR occurs with a shift in the localization of ZO-1 from a TJ/apical to a more intracellular one [ 32 ]. These data are also consistent with multiple reports of abnormal TJ formation caused by mutant CFTR [ 29 , 30 , 33 ], as well as with the proposal that functional CFTR interacts directly with ZO-1 to regulate TJ formation [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…However, we also show that in CF epithelia, the TJ protein ZO-1 shows intracellular and diffuse staining and, although SLC26A9 and ZO-1 still appear to co-localize, the integrity of TJ structures is compromised. This is in line with our previous findings (both in lung tissue and immortalized CFBE cells) demonstrating that the presence of mutant CFTR occurs with a shift in the localization of ZO-1 from a TJ/apical to a more intracellular one [ 32 ]. These data are also consistent with multiple reports of abnormal TJ formation caused by mutant CFTR [ 29 , 30 , 33 ], as well as with the proposal that functional CFTR interacts directly with ZO-1 to regulate TJ formation [ 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Also consistent with these data on diffuse SLC26A9 expression at the compromised TJ structures in CF [ 32 ], our results in CF (F508del/F508del) pHNE cells also suggest a delayed expression of SLC26A9 over the course of differentiation vs. control cells. Moreover, our data indicate that lower SLC26A9 expression levels may affect cell polarization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…First, CF explants analyzed for EMT markers exhibit increased gene expression for ACTA2, VIM, and COL1A1 and increased protein levels for vimentin and N-cadherin. Similarly, CFBE F508del-CFTR cells cultured in ALI display decreased TEER, along with increased vimentin, N-cadherin, and collagen-1 protein levels ( Quaresma et al, 2020 ). The same study also demonstrates that the presence of (functional) CFTR confers a resistance to TGF-β1-induced EMT, as wt-CFTR cell lines exposed to TGF-β1 show reduced TGF-β1-induced EMT markers as compared with CF mimicking F508del-CFTR cell line.…”
Section: Epithelial Alterations In Chronic Respiratory Diseasesmentioning
confidence: 99%
“…The same study also demonstrates that the presence of (functional) CFTR confers a resistance to TGF-β1-induced EMT, as wt-CFTR cell lines exposed to TGF-β1 show reduced TGF-β1-induced EMT markers as compared with CF mimicking F508del-CFTR cell line. It also revealed that impaired CFTR may lead to EMT in a Twist Family BHLH Transcription Factor 1 (TWIST1)-related manner ( Quaresma et al, 2020 ). In parallel, CF-derived cell lines exhibit increased fibronectin ( Nyabam et al, 2016 ).…”
Section: Epithelial Alterations In Chronic Respiratory Diseasesmentioning
confidence: 99%